Ethanolic Extract of Papaya (Carica papaya) Leaves Improves Blood Cholesterol Profiles and Bone Density in Ovariectomized Rats - Sugiyanto, Raisatun Nisa; Khamsita, Rahmi; Susidarti, Ratna Asmah (Indonesian Research Gateway, 2012)
Bone loss and disturbance in the blood cholesterol profiles modulation are two effects caused by menopauses syndromes. As the estrogen concentration in the body decreased drastically, menopause women need the replacement of estrogen to keep the regulation of several physiological functions in the body, such as bone generation and cholesterol regulation in a good condition. Phytoestrogen in Carica papaya leaves, such as quercetin, could be one of the potential agents for the estrogenic effect. The aim of this study is to know the effects of papaya leaf extract (PLE) on the blood cholesterol profiles and bone density in ovariectomized rats. Thirty six female Sprague Dawley rats divided into six groups. The groups were sham-treated ovx (S-OVX), ovariectomized rats (OVX), CMC-Na control (OVX+CMC-Na), positive control (OVX+Estradiol), and the PLE treatment groups dose 750 mg/kgBW (OVX+750mg/kgBW) and dose 1000 mg/kgBW (OVX+1000 mg/kgBW). Administrations of PLE were done in three weeks orally and estradiol administrated intraperitonially. In the end of the treatment, the blood sample of tested animals was collected for the blood cholesterol determination (LDL, HDL, triglyceride, and total cholesterol) and the femur bones were examined for the bone density. Based on the results, PLE dose of 750 mg/kgBW a day in ovariectomized rats showed estrogenic effects in modulating blood cholesterol profile by lowering total cholesterol levels. Meanwhile, PLE dose of 1000 mg/kgBW significantly increased the bone density (p<0.05). Thus, PLE is potential to overcome the negative effects of post-menstrual women especially in the cholesterol blood profiles and bone density.Keywords : Carica papaya, phytoestrogen, bone density, blood cholesterol, ovariectomized rats